The Effects of Platelet-Activating Factor on Uterine Contractility, Perfusion, Hypoxia, and Pain in Mice. (March 2018) - Hellman, Kevin M.; Yu, Peter Y.; Oladosu, Folabomi A.; Segel, Chaya; Han, Alice; Prasad, Pottumarthi V.; Jilling, Tamas; Tu, Frank F.
It is widely hypothesized that menstrual pain is triggered by prostaglandin synthesis that evokes high-pressure uterine contractions and ischemia. However, the effects of molecules implicated in menstrual pain on uterine contractility, perfusion, and oxygenation in vivo have been rarely demonstrated. Studies in women that do not respond to nonsteroidal anti-inflammatory drugs (NSAIDs) have reported elevated levels of platelet-activating factor (PAF). To establish in vivo evidence of PAF's capability to impair uterine homeostasis and to elicit visceral pain, we examined the effects of the PAF receptor agonist (carbamyl PAF [CPAF]) in comparison to other molecules hypothesized to play a role in uterine pain in mice. Uterine pressure was increased by oxytocin, prostaglandin F2α (PGF2α), and CPAF. Even in the absence of inflammatory molecules, uterine contractions reduced uterine oxygenation by 38%. CPAF reduced uterine perfusion by 40% ± 8% and elicited further oxygen desaturation approaching hypoxia (9.4 ± 3.4 mm Hg Pao 2 ). Intraperitoneal injections of CPAF and PGF2α evoked visceral pain and pelvic hyperalgesia in awake wild-type mice. However, pain was not observed in identically injected PAF-receptor knockout mice. Thus, our model provides a demonstration that a molecule implicated in NSAID-resistant dysmenorrhea has a detrimental effect on uterine homeostasis and is capable of causing visceral pain. Our results support the general hypothesis that menstrual cramps are caused by uterine contractions, impaired perfusion, and reduced oxygenation. Since this study was limited to mice, confirmation of these results in humans would be valuable for development of novel therapeutics targeted at inflammatory precursors, contractility, perfusion, and tissue oxygenation.